Comparison of the performance of chitosan and a cationic polyacrylamide as flocculants of emulsion systems - Pinotti, Adriana Noemí (2001)
Food industries contribute significantly to the pollution of water streams. Oil in wastewaters must be removed to prevent fouling of process equipment, to reduce interference with subsequent water-treatment units, and to comply with water-discharge requirements. Polyelectrolytes are frequently used to coagulate and flocculate colloidal systems. A model system of a sunflower oil/water emulsion was used to analyze the effect of: (i) emulsion droplet sizes, (ii) surfactant chain length (sodium dodecyl sulfate and sodium tetradecyl sulfate), (iii) ionic strength, and (iv) pH, on the doses of chitosan (natural cationic polyelectrolyte) and a cationic polyacrylamide, necessary to neutralize electrical charge and to get flocculation. Methods used were: turbidimetry, jar test, colloidal titration, and light microscopy observation. Results showed that the increase of NaCl concentration reduces the doses of chitosan and polyacrylamide to reach zero colloidal charge; these doses increase with the surfactant chain length. pH variation did not show any influence on the chitosan dose necessary to flocculate the system. Redispersion of the emulsion was observed in chitosan and polyacrylamide treatments.